A case report—“When less is more”: controlled inpatient reduction of anticholinergic burden in a patient with clozapine-resistant schizophrenia - Pjevac, Milica; Korošec Hudnik, Liam (Frontiers in Psychiatry, 2023)
The functional status of an individual with schizophrenia is the defining factor in their quality of life and is closely associated with cognitive abilities, which are impaired in individuals with schizophrenia and considered to be the core symptom of the disorder. The use of psychopharmacotherapy can also have a significant impact on cognitive functioning. The relationship between clozapine treatment and cognitive impairment in individuals with schizophrenia is an intricate one. While some studies have reported a positive effect of clozapine on learning and memory, other studies have found that patients treated with clozapine experienced a decline in cognitive functioning in particular areas. In particular, attention and memory have been shown to deteriorate with rising plasma levels of clozapine. This effect may be attributed to its anticholinergic effect. A reduction in the medication related to anticholinergic burden has been previously found to improve cognitive abilities. In the presented case, we describe a psychotic relapse with delirium symptoms in a patient on clozapine treatment with potentially toxic clozapine blood level. The symptoms of delirium subsided after a clozapine dose adjustment. Gradually lowering the initially very high anticholinergic burden improved the patient's cognitive functioning.